2022
DOI: 10.1111/ddg.14638_g
|View full text |Cite
|
Sign up to set email alerts
|

Phänotypisches und genetisches Spektrum von Incontinentia pigmenti – eine große Fallserie

Abstract: ZusammenfassungHintergrundIncontinentia pigmenti ist eine seltene X‐chromosomal dominant vererbte Systemerkrankung, die vor allem die Haut, aber auch andere neuroektodermale Gewebe wie Zähne, Haare, Augen und das zentrale Nervensystem betrifft.Patienten und MethodikDiese multizentrische Fallserienstudie wurde an drei europäischen Hautkliniken durchgeführt und umfasste 30 Patienten mit Incontinentia pigmenti. Zwanzig Patienten wurden klinisch und genetisch untersucht, weitere zehn nur genetisch.ErgebnisseDie St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, the sister of the proband in the first family had repeated episodes of erythema and blisters on the trunk throughout almost one full year of follow-up, which may be related to residual mutant keratinocyte hyperproliferation and inflammation. Previous studies have shown that ocular abnormalities are often accompanied by neurological manifestations and determine the severity of IP ( 8 ). Therefore, we recommend close follow-up for the progression of IP-related diseases and appropriate imaging studies as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sister of the proband in the first family had repeated episodes of erythema and blisters on the trunk throughout almost one full year of follow-up, which may be related to residual mutant keratinocyte hyperproliferation and inflammation. Previous studies have shown that ocular abnormalities are often accompanied by neurological manifestations and determine the severity of IP ( 8 ). Therefore, we recommend close follow-up for the progression of IP-related diseases and appropriate imaging studies as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%